Perlindungan Hukum terhadap Penyandang Disabilitas Mental dalam Pemilihan Umum - Evanglis A. L. Tompoliu; Wenly R. J. Lolong; Merry L. Kumajas (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study examines legal protection for persons with mental disabilities in general elections as part of efforts to guarantee their equal political rights. Although these rights are guaranteed in the constitution and various regulations, obstacles remain in the implementation of inclusive election policies. Various obstacles, such as limited access to election information, lack of supporting facilities at polling stations, and inherent social stigma, often hinder the participation of persons with mental disabilities in the democratic process. The approach used in this study is normative juridical, analyzing laws and regulations and examining field practices. The results indicate that despite clear legal protection, its implementation remains far from ideal due to various technical and social barriers. Furthermore, violations of voting rights for persons with mental disabilities are still encountered. To address these issues, the study recommends a more inclusive election system, increasing the capacity of election officials to handle voters with disabilities, and providing more effective support mechanisms.